2010
DOI: 10.1089/jmf.2009.1128
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Factor κB Activation and Cyclooxygenase-2 Expression by Aqueous Extracts of Hispanic Medicinal Herbs

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are a primary choice of therapy for diseases with a chronic inflammatory component. Unfortunately, long-term NSAID therapy is often accompanied by severe side effects, including cardiovascular and gastrointestinal complications. Because of this, there is critical need for identification of new and safer treatments for chronic inflammation to circumvent these side effects. Inflammatory diseases have been successfully remedied with natural herbs by many cultures. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…20 NSAIDs are used for treating inflammatory diseases. 21,22 The results of this study showed that intraperitoneal injection of LPS could cause alteration in hematological parameters, as the level of WBC in LPS group significantly reduced, and pretreatment with diclofenac could not restore these parameters to normal levels ( Table 1). The post-endotoxin leukopenia mainly resulted from a decrease in circulating neutrophil count.…”
Section: Resultsmentioning
confidence: 86%
“…20 NSAIDs are used for treating inflammatory diseases. 21,22 The results of this study showed that intraperitoneal injection of LPS could cause alteration in hematological parameters, as the level of WBC in LPS group significantly reduced, and pretreatment with diclofenac could not restore these parameters to normal levels ( Table 1). The post-endotoxin leukopenia mainly resulted from a decrease in circulating neutrophil count.…”
Section: Resultsmentioning
confidence: 86%
“…Conventional analgesics play an important role in pain therapy, but they always cause kinds of adverse effects during clinic use [2]. The same as the analgesics, nonsteroidal anti-inflammatory drugs (NSAIDs) are the primary therapy for diseases with a chronic inflammatory response, but long-term use often causes severe side effects, including cardiovascular and gastrointestinal complications that limit their development [3, 4]. Therefore, the research for new analgesic and anti-inflammation agents are critically needed.…”
Section: Introductionmentioning
confidence: 99%
“…Salicyclic acid and glucocorticoid may inhibit the activation of NF-κB or COX-2. 19,20 Folic acid (FA) supplementation during pregnancy reduces the risk of neural tube defects, but it may be used to prevent preterm labor and intrauterine growth restriction (IUGR). FA significantly reduced interleukin-6 and keratinocyte-derived cytokine in the amniotic fluid of LPS-treated mice.…”
Section: Discussionmentioning
confidence: 99%